Multimodality approach to diagnose gastric diverticulum: a rare cause of acute abdomen - M. Y., Rizal; Nor Hanipah, Zubaidah; A. H ., Shaker (Universiti Putra Malaysia, 2022)
Gastric Diverticulum (GD) is a rare form of diverticular disease where it is defined as out-pouching of gastric wall. Majority of patients are asymptomatic but it may present with variable symptoms mimicking other diseases. We report a case of GD mimicking sealed perforated gastric ulcer based on clinical presentation and Contrast-Enhanced Computed Tomography (CECT) abdomen images.